Pemanfaatan Bahan Alam sebagai Sumber Daya Kosmetik untuk Perawatan di Kelurahan Sungai Tiung Kecamatan Cempaka - Dyera Forestryana; Wahyudin Bin Jamaludin; Ratna Restapaty; Hafiz Ramadhan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Today, many cosmetic products are unhealthy and un-quality. Nowadays, the lifestyle trend of "back to nature" is increasing where people's trust in active compounds of natural materials is relatively safer than synthetic chemical compounds. Therefore, creating healthy and quality products at affordable prices is the focus of the government. Cosmetics are ingredients or preparations intended for use on the outside of the human body (epidermis, hair, nails, lips, and outer genital organs) or teeth and mucous membranes of the mouth, especially to cleanse, scent, change the appearance, and or improve body odor or protect or maintain the body in good condition. The activities that will be carried out are a demonstration of the manufacture of cosmetics of natural materials by a team of lecturers to the community in The Village of Sungai Tiung, Cempaka, Banjarbaru to improve the quality of public health knowledge and insights towards the training of cosmetic natural materials so that people can use the natural ingredients around as cosmetics and have a selling value, such as rose water, masks, and body butter. So that the cosmetic natural ingredients have the potential to be developed into natural mask ingredients for the face. It is expected that residents can use coffee, green tea, rose petals, oats, and rice as natural cosmetic ingredients for treatment and can increase their economic value as a business opportunity.